1997
DOI: 10.1159/000291842
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxytocin, Prostaglandin F<sub>2α</sub> and Prostaglandin E<sub>2</sub> on Intracellular Free Calcium Concentrations of Longitudinal Muscle Cells Isolated from Term Pregnant Rat Myometrium

Abstract: The effects of oxytocin, PGF and PGE2 on [Ca2+]i of isolated longitudinal muscle cells of term pregnant rats were investigated using Fura-2. Oxytocin, PGF and PGE2 induced an initial rapid increase followed by a secondary gradual increase in [Ca2+]i in the presence of 1.5 mM Ca2+. The initial maximum increases in [Ca2+]i were obtained at 6 s for oxytocin, 20 s for PGF and 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…The L-type Ca 2+ channel is well known to be a major pathway for Ca 2+ influx during uterine contractions. 10 13 Its expression was increased by 2.5-fold in the odontogenic infection model mice in the present study, suggesting enhanced electrical excitability of the myometrial cells. These findings support that odontogenic infection in mice is useful as a model of preterm delivery induced by inflammation.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The L-type Ca 2+ channel is well known to be a major pathway for Ca 2+ influx during uterine contractions. 10 13 Its expression was increased by 2.5-fold in the odontogenic infection model mice in the present study, suggesting enhanced electrical excitability of the myometrial cells. These findings support that odontogenic infection in mice is useful as a model of preterm delivery induced by inflammation.…”
Section: Discussionsupporting
confidence: 63%
“…The main source of Ca 2þ is thought to be Ca 2þ influx through L-type Ca 2þ channels and receptor-operated nonselective cation channels (NSCCs). [10][11][12][13] In addition, myometrial NSCCs play an important role in changing the membrane potential to induce spontaneous uterine contractions. We previously identified that the purinergic receptor P2X7 is one of the myometrial NSCCs in the rat uterus.…”
Section: Introductionmentioning
confidence: 99%
“…The best known uterine contracting agents, e.g. oxytocin and prostaglandins, lose their effects after removal of the extracellular Ca 2ϩ [19]. The smooth muscle contraction therefore depends greatly on the amount of extracellular Ca 2ϩ ions entering the cell.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the present study was to characterize the ability of such uterine tissues to contract in response to EFS in late pregnancy (days [15][16][17][18][19][20][21][22] in the rat. For this purpose, we set out to describe the contractility by choosing stimulation parameters necessary to elicit rhythmic contractions.…”
Section: Introductionmentioning
confidence: 99%